2005
DOI: 10.1002/eji.200535138
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulator ginsan induces resistance to experimental sepsis by inhibiting Toll‐like receptor‐mediated inflammatory signals

Abstract: Ginsan, a polysaccharide extracted from Panax ginseng, has multiple immunomodulatory effects. In this study, we show that pretreatment of ginsan (25 lg/kg) protected mice from lethality induced by Staphylococcus aureus challenge. This survival benefit was associated with enhanced bacterial clearance from circulation, spleen and kidney. The phagocytic activity of macrophages treated with ginsan was significantly enhanced against S. aureus. However, the production of proinflammatory cytokines, such as TNFa, IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(86 citation statements)
references
References 43 publications
3
82
1
Order By: Relevance
“…If so, this medicinal herb might be expected to benefit individuals infected with microbial pathogens by limiting the production of inflammatory mediators such as TNF-α and IL-6 without affecting the generation of pathogen-specific adaptive immunity. This possibility is consistent with a previous report demonstrating that notoginseng-treated mice were less susceptible to the ill effects of experimental sepsis, effects which the authors attributed to a decreased inflammatory response to infection (Ahn et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…If so, this medicinal herb might be expected to benefit individuals infected with microbial pathogens by limiting the production of inflammatory mediators such as TNF-α and IL-6 without affecting the generation of pathogen-specific adaptive immunity. This possibility is consistent with a previous report demonstrating that notoginseng-treated mice were less susceptible to the ill effects of experimental sepsis, effects which the authors attributed to a decreased inflammatory response to infection (Ahn et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…These limited nonspecific protective effects are consistent with results from previous studies demonstrating that pretreatment with ginseng polysaccharide showed survival advantages against experimental bacterial sepsis. 25,26 Ginseng treatment after infection showed lesser protective effects compared with those before infection. Consistent with our study, it was previously reported that saponins from ginseng extract suppressed the delayed-type hypersensitivity responses to the H1N1 influenza A/WSN virus when administered to the animals before but not after virus sensitization.…”
Section: Discussionmentioning
confidence: 93%
“…41 Also, time-dependent effects of treatment with ginseng (or ginseng polysaccharides) were observed previously. 24,26 In clinical studies, the incidence of common cold symptom complex or acute respiratory infection was also significantly lower in healthy individuals who had preventively taken ginseng. 29,42 The results in this study support the protective effects of ginseng against influenza virus infection when taken in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polysaccharide extracts from Panax ginseng can increase immunity and enhance chemotherapy [129][130][131] . There is evidence of interaction with TLRs, especially TLR4 136,137,148 .…”
Section: Herbsmentioning
confidence: 99%